PENGEMBANGAN PENUNTUN PRAKTIKUM LARUTAN ELEKTROLIT DAN NONELEKTROLIT DI SMA NEGERI 1 RASAU JAYA - Fatmawati Fatmawati; Dini Hadiarti; Dedeh Kurniasih; Rizmahardian Anshari Kurniawan (Universitas Muhammadiyah Pontianak, 2019)
A practical guide is an important role in conducting an effective practicum class. It helps students to take part in the activities in accordance with the learning goals. Therefore, this study aimed to develop a practical guide of electrolyte and nonelectrolyte solutions for students of SMA Negeri 1 Rasau Jaya. Using an R & D model of Borg and Gall, seven out of eleven stages of material design were employed. The stages used in this study were research and data collection, planning, draft development, initial product trial, initial product revision, main field trial, and revision of operational products. The data collection technique used were observation, questionnaire, and measurement. The instruments were observation and questionnaire sheet, and posttest question. The study revealed that the practically gathered from the teacher questionnaire was 91,0% and from the student’s response was 83,1%. The effectiveness of the practical guide was 91,8%. Hence, the practical guide of electrolyte and nonelectrolyte solutions for students of SMA Negeri 1 Rasau Jaya is effective and valid. Therefore, it can be concluded that a practical guide is highly recommended to be used in the practicum class.